2006
DOI: 10.1002/ijc.22242
|View full text |Cite
|
Sign up to set email alerts
|

TANGO is a tumor suppressor of malignant melanoma

Abstract: The TANGO gene was originally identified as a new family member of the melanoma inhibitory activity gene family. The gene codes for a 14 kDa protein of so far unknown function. In our study we revealed that TANGO was downregulated or lost in 9 melanoma cell lines when compared to normal melanocytes and in most of the 8 tumor samples analyzed. The losses were associated with advanced stage of the disease. These results were confirmed in situ by immunohistochemistry on 10 paraffin-embedded sections of human mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…MIA3, also referred to as ARNT or TANGO, belongs to the melanoma inhibitory activity gene family and may have a role in tumor suppression. 24,25 As with the case of rs1333049, the classic risk factors appear not to be related to the increased MI risks associated with rs17465637.…”
Section: Discussionmentioning
confidence: 84%
“…MIA3, also referred to as ARNT or TANGO, belongs to the melanoma inhibitory activity gene family and may have a role in tumor suppression. 24,25 As with the case of rs1333049, the classic risk factors appear not to be related to the increased MI risks associated with rs17465637.…”
Section: Discussionmentioning
confidence: 84%
“…We initiated this study because we recently found that TANGO is reduced in malignant melanoma and has a tumor suppressor role in this kind of tumor (14). Specifically, we were interested whether TANGO plays a similar role also in other tumors and, therefore, analyzed the expression of TANGO in colon carcinoma and HCC and whether treatment with TANGO may change the migratory and invasive activity of the colon and hepatoma tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the staining was performed semiquantitatively by light-microscopy. The method was described elsewhere (14).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations